(untitled) (Journal of Hama University, 2022)
Comparison of the efficacy of a 3D-Bimetric Maxillary Arch and a Pendulum Appliance to Space Regaining in Late Mixed Dentition Period. The research sample consisted of / 14 / patients divided into two groups, each group consisted of 7 patients for comparison between the two appliances, with a mean age of the sample 10.5 ± 6 months, lateral radiographs of the head (Cephalometric) were taken before and a month and a half after space regaining in order to evaluation the changes taking place. The results of the current study showed the superiority of the 3D –Bimetric with a statistically significant difference with an average of 1.29 mm over a Pendulum Appliance with an average of 0.38 in creating the lateral displacement and space regaining through the application of bodily movement on the permanent upper first molar. We conclude from the current study that the 3D-Bimetric Maxillary Arch was superior to the Pendulum Appliance with a statistically significant difference in creating the lateral displacement and space regaining.